Effect of suppression of arabinoxylan synthetic genes in wheat endosperm on chain length of arabinoxylan and extract viscosity. Issue 1 (27th March 2015) - Freeman, Jackie; Lovegrove, Alison; Wilkinson, Mark David; Saulnier, Luc; Shewry, Peter Robert; Mitchell, Rowan Andrew Craig
Summary: Arabinoxylan (AX) is the dominant component within wheat ( Triticum aestivum L.) endosperm cell walls, accounting for 70% of the polysaccharide. The viscosity of aqueous extracts from wheat grain is a key trait influencing the processing for various end uses, and this is largely determined by the properties of endosperm AX. We have previously shown dramatic effects on endosperm AX in transgenic wheat by down‐regulating either TaGT43_2 or TaGT47_2 genes (orthologues to IRX9 and IRX10 in Arabidopsis, respectively) implicated in AX chain extension and the TaXAT1 gene responsible for monosubstitution by 3‐linked arabinose. Here, we use these transgenic lines to investigate the relationship between amounts of AX in soluble and insoluble fractions, the chain‐length distribution of these measured by intrinsic viscosity and the overall effect on extract viscosity. In transgenic lines expressing either the TaGT43_2 or TaGT47_2 RNAi transgenes, the intrinsic viscosities of water‐extractable (WE‐AX) and of a water‐insoluble alkaline‐extracted fraction (AE‐AX) were decreased by between 10% and 50% compared to control lines. In TaXAT1 RNAi lines, there was a 15% decrease in intrinsic viscosity of WE‐AX but no consistent effect on that of AE‐AX. All transgenic lines showed decreases in extract viscosity with larger effects in TaGT43_2 and TaGT47_2 RNAi lines (by up to sixfold) than in TaXAT1 RNAi lines (by twofold). These effects were explained by the decreases in amount and chain length of WE‐AX, with decreases in amount having the greater influence. Extract viscosity from wheat grain can therefore be greatly decreased by suppression of single gene targets.